The Study and Analysis of Cell Phone Charging Modules in Nigeria - Efenedo, G. I.; Okpare, A. O.; Efenedo, O. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Cellular phones require frequent charging with the aid of modules known as chargers. The performance of chargers in Oleh, a community in the Niger Delta area of Nigeria as a case study were investigated with a view to proffering solutions arising from the conventional act of disposing failed chargers without attempted remedies by users. Twenty (20) chargers were sampled and examined to determine the electronic components most likely prone to failure in the modules and possible reactivation. Also, experiments were performed to compare charging rates to initial specifications by manufacturers for the sampled chargers. The results show that the components most likely prone to failure from the sampled chargers in order of frequency of failure were circuit breakers, capacitors, switching rectifier and switching power transistors. Furthermore, one of the reactivated chargers model, Infinix of initial specification mostly available in Nigeria with open-circuit voltage of 5.00V and short-circuit current of 1500mA, recorded 4.50V, 800mA and was able to charge Samsung A12 phone to full capacity (100%) in twenty(20) minutes at a charging rate of 0.01V.min or -4.67A/min respectively. Similarly, reactivated Oraimo charger recorded 4.70.00V, 2500mA as against 5.00V, 900mA specifications when charging the Tecno Pop2 phone. The results show that the reactivated modules charging performances were comparatively enhanced at current delivery to loads as shown by the two cell phones. Therefore, it is recommended that Engineers and Technicians skills be chandelled towards local design and reactivation of failed charging modules in Nigeria.